2022
DOI: 10.21037/hbsn-19-870
|View full text |Cite
|
Sign up to set email alerts
|

Gd-EOB-DTPA-enhanced MRI radiomic features for predicting histological grade of hepatocellular carcinoma

Abstract: Background: Prediction models for the histological grade of hepatocellular carcinoma (HCC) remain unsatisfactory. The purpose of this study is to develop preoperative models to predict histological grade of HCC based on gadolinium-ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA)-enhanced magnetic resonance imaging (MRI) radiomics. And to compare the performance between artificial neural network (ANN) and logistic regression model. Methods: A total of 122 HCCs were randomly assigned to the trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Wu et al [ 30 ] found that MRI-based radiomics can successfully categorize low-grade and high-grade HCC, with the radiomic model outperforming the clinical model (AUC 0.742 for the combined T1-weighted and T2-weighted MRI-based radiomic model vs AUC 0.6 for the clinical one) and the combined radiomic and clinical model (AUC 0.8) outperforming both models alone. Mao et al [ 31 ] also investigated MRI-based radiomic features, with Gd-EOB-DTPA contrast administered for the MRI exams, finding that the artificial neural network combining radiomic features from the contrast-enhanced arterial phase and hepatobiliary phase yielded the highest AUC of 0.944. Moreover, they found that the artificial neural network models were superior to the logistic regression models.…”
Section: Applications Of Radiomics In Hccmentioning
confidence: 99%
“…Wu et al [ 30 ] found that MRI-based radiomics can successfully categorize low-grade and high-grade HCC, with the radiomic model outperforming the clinical model (AUC 0.742 for the combined T1-weighted and T2-weighted MRI-based radiomic model vs AUC 0.6 for the clinical one) and the combined radiomic and clinical model (AUC 0.8) outperforming both models alone. Mao et al [ 31 ] also investigated MRI-based radiomic features, with Gd-EOB-DTPA contrast administered for the MRI exams, finding that the artificial neural network combining radiomic features from the contrast-enhanced arterial phase and hepatobiliary phase yielded the highest AUC of 0.944. Moreover, they found that the artificial neural network models were superior to the logistic regression models.…”
Section: Applications Of Radiomics In Hccmentioning
confidence: 99%
“…In this study, 3D slicer (version 4.11.20210226, https://www.slicer.org/ ) image segmentation software was used to delineate the region of interest (ROI) of GP-NENs masses, including plain scan, arterial phase, and venous phase CT data, and followed by texture analysis and data extraction. After determining the candidate texture data such as firstorder, glcm, and ngtdm, R (version 4.1.3) was then used to perform cross-validation and Lasso coefficients regression on the above texture data to extract valid texture data and generate radiomic score (Radscore) values [ 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…30 Several studies have constructed radiomics models using HBP radiomics features that could predict tumor differentiation grade. 37,38 Wu et al found that a radiomics signature based on T1-weighted imaging and T2-weighted imaging can successfully categorize low-grade and high-grade HCC. 39 MTM-HCC has received significant attention in recent years, which is an aggressive subtype associated with angiogenesis and immunosuppressive tumor microenvironment.…”
Section: Mri-based Radiomics For Hccmentioning
confidence: 99%
“…The hepatobiliary phase (HBP) of DCE‐MRI with Gd‐EOB‐DTPA is particularly useful for evaluating liver tumors, as it has been shown to provide important information about tumor aggressiveness 30 . Several studies have constructed radiomics models using HBP radiomics features that could predict tumor differentiation grade 37,38 . Wu et al found that a radiomics signature based on T1‐weighted imaging and T2‐weighted imaging can successfully categorize low‐grade and high‐grade HCC 39 .…”
Section: Mri‐based Radiomics For Hccmentioning
confidence: 99%